(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper makes analyses on the essence and principles of regional economic policy at the present stage. Therefore, both theoretical and analytical analyses were conducted. It concluded with outcomes and shortcomings of the essence and principles of regional economic policy at the present stage.